Program Psikososial di Bangsal Kanker Anak Rumah Sakit Kanker "Dharmais" - Edi Setiawan Tehuteru; Raden Citra Kusumarojo (Indonesian Journal of Cancer)
Even though sick, children that being treated should be kept monitored regarding their growth and development. To meet this requirement, Children Cancer Ward in "Dharmais" National Cancer Center use psychosocial approach other than medical approach. Through this approach, we hope that we are able to facilitate the growth and development in these children who suffer from cancer. The objective ofthis paper is to show how the psychosocial program carried out in "Dharmais" National Cancer Center. The psychosocial program starts on July 2006, run by volunteers who gathered in the Community for Children with Cancer. These programs include giving information regarding the disease and treatment of cancer in children to parents and the patient itself, accompanying children during direct process of diagnostic and treatment, making activities for patient, such as playground activity, art therapy, school in hospital, bed side, art therapy, and computer therapy. These activities will keep the children from being afraid during the treatment and enable them to keep on playing properly like any other healthy children. The result from this approach is to enable children to be handled in a holistically way and it is important that these programs can facilitate the process of their growth and development.